The case of the cryptic crinoline eaudiobook - Springer, Nancy (Enola Holmes, 2011)
Don't miss Enola Holmes: The Case of the Missing Marquess! A Netflix original movie starring Millie Bobby Brown, Henry Cavill, and Helena Bonham Carter! Enola Holmes—younger sister to Sherlock Holmes—is back on another case! Enola Holmes's landlady, Mrs. Tupper, is the closest thing Enola has to family these days, besides her occasional run-ins with her brother Sherlock. Even though Mrs. Tupper is nearly deaf and can barely cook, she's an endearing presence as Enola longs for her absent mother. So imagine her horror when Enola comes home to find Mrs. Tupper kidnapped! Who would take her, and why? And what does Florence Nightingale have to do with it? From the master of mystery Nancy Springer, here's another absorbing adventure for our award-winning, unstoppable heroine, Enola Holmes.